Pengaruh Electronic Word of Mouth (E-Wom) Customer Engagement dan Customer Experience Terhadap Loyalitas Pelanggan Produk Fashion Muslim di E-Commerce Shopee pada Gen Z Muslim Kota Bengkulu - Lia Elenda; Noni Afrianty; Citra Liza (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2026)
This study aims to examine the influence of Electronic Word of Mouth (eWOM), customer engagement, and customer experience on customer loyalty toward Muslim fashion products on Shopee e-commerce among Muslim Generation Z in Bengkulu City. This research employed a quantitative approach with a causal research design. The population consisted of Muslim Generation Z consumers in Bengkulu City who use Shopee and have purchased Muslim fashion products. The sample comprised 100 respondents selected using the Slovin formula and purposive sampling technique. Data were collected through a questionnaire distributed via Google Forms to respondents who met the research criteria. The collected data were analyzed using multiple linear regression with the assistance of SPSS version 27. The results indicate that Electronic Word of Mouth (eWOM) has a positive and significant effect on customer loyalty. Customer engagement also has a positive and significant effect on customer loyalty. Likewise, customer experience has a positive and significant effect on customer loyalty. Furthermore, Electronic Word of Mouth (eWOM), customer engagement, and customer experience simultaneously have a positive and significant effect on customer loyalty toward Muslim fashion products on Shopee e-commerce among Muslim Generation Z in Bengkulu City.